Pendampingan Kegiatan Belajar Siswa dengan Memanfaatkan Barang Bekas untuk Meningkatkan Minat dan Kreativitas Belajar Siswa pada Era Covid-19 - Nur Roikhatul Jannah; Wiwied Pratiwi; Rosaila Umikulsum (Bulletin of Community Engagement, 2021)
The article gave learning assistance by students’ utilizing waste to increase students' interest and creativity. This research used ABCD (Asset Based Community Development) method. Five steeps to conduct this research; discovery, dream, design, define, and destiny. As for this research method including: preparation stage consisting of observation, interview to parents of students, delivery of strategies, and material extension, implementation stage consisting of socialist implementation of activities initiated by approach and mentoring students, evaluation stage of assessment of activities that have been carried out. The results activities showed that the students learning assistance against corona virus and utilizing used goods as a place to wash hands, mentoring students in utilizing waste to make product handicrafts, and mentoring students in utilizing waste as a learning medium. Keywords: Utilizing Waste, Assistance Learning Activity, Creativity in Covid-19 Era